2020
DOI: 10.1002/lary.29345
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vertical Stiffness Gradient on the Maximum Divergence Angle

Abstract: Introduction: During vocal fold vibration, the medial surface of both folds forms a convergent shape during opening and a divergent shape during closing. A greater maximum divergence angle is associated with greater closing forces which will increase the closing speed of the glottis. An increased closing speed results in a greater acoustic intensity and greater vocal efficiency. Indentation testing showed that as the strain increases, the inferior aspect of the folds becomes stiffer than the superior aspect, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…We observed that at low Psg, when FSV is smaller, the difference in circulation strength, and thus its impact on phonation, is less pronounced than at high Psg. This association between greater VE and stronger FSV was shown in a previous study using the excised canine larynx model 29 …”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…We observed that at low Psg, when FSV is smaller, the difference in circulation strength, and thus its impact on phonation, is less pronounced than at high Psg. This association between greater VE and stronger FSV was shown in a previous study using the excised canine larynx model 29 …”
Section: Discussionsupporting
confidence: 82%
“…This association between greater VE and stronger FSV was shown in a previous study using the excised canine larynx model. 29 Clinically, increased VE translates to easier, more sustainable phonation. This reduced efficiency causes increased vocal fatigue, a common complaint of UVFP patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerodynamic analysis of the wet larynx has not been conducted previously. During phonation, the glottis shape in the mid‐coronal plane is convergent during opening and divergent during closing 13 . This is caused by a phase delay between the inferior and superior edges of the vocal folds known as a vertical phase difference (VPD).…”
Section: Introductionmentioning
confidence: 99%